2022
DOI: 10.1186/s12873-022-00646-0
|View full text |Cite
|
Sign up to set email alerts
|

Using mobility status as a frailty indicator to improve the accuracy of a computerised five-level triage system among older patients in the emergency department

Abstract: Background Owing to societal ageing, the number of older individuals visiting emergency departments (EDs) has increased in recent years. For this patient population, accurate triage systems are required. This retrospective cohort study assessed the accuracy of a computerised five-level triage system, the Taiwan Triage and Acuity System (TTAS), by determining its ability to predict in-hospital mortality in older adult patients and compare it with the corresponding rate in younger adult patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…How to identify critically ill patients at an early stage under high load and improve the accuracy of triage and evaluation is particularly important. At present, the emergency prediction of critically ill patients mostly adopts vital sign assessment method, NEWS, emergency pre-examination and triage expert consensus, adult velevel emergency triage system and so on [11][12] . In each scoring table, those with fewer indicators are convenient to use, but their accuracy may be poor, while those with more indicators improve their accuracy, but the indicators are not easy to obtain, which prolongs the triage time.…”
Section: Discussionmentioning
confidence: 99%
“…How to identify critically ill patients at an early stage under high load and improve the accuracy of triage and evaluation is particularly important. At present, the emergency prediction of critically ill patients mostly adopts vital sign assessment method, NEWS, emergency pre-examination and triage expert consensus, adult velevel emergency triage system and so on [11][12] . In each scoring table, those with fewer indicators are convenient to use, but their accuracy may be poor, while those with more indicators improve their accuracy, but the indicators are not easy to obtain, which prolongs the triage time.…”
Section: Discussionmentioning
confidence: 99%
“…The TTAS was adapted from the CTAS and has been widely used in every EDs in Taiwan [ 18 ]. Despite the overall validity and reliability of the TTAS, it lacks a modifier for older patients [ 29 , 30 ]. Ng et al have reported that the incorporation of the CFS into TTAS has the potential to reduce the under-triage of older adults in the ED [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is the common opinion of the authors that 5LTs, due to their increased accuracy and safety, are better than 3LT or 4LT systems. The fact that this advantage also affects geriatric patients has not yet been widely studied [3,8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%